Tillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/Double-Crop Soybean Rotation - D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 2015)
In 2013, late planting resulted in corn yields that were less than 100 bu/a. Nitrogen (N) placement did not affect yields in the higher-yielding conventional tillage system, but knifing tended to result in greater yield in reduced and no-till systems.
Keywords: tillage; nitrogen placement; short-season rotation; corn yield; wheat yield; soybean yield